Unravelling students’ emotions of online learning during the pandemic through metaphors - Venita Risadilla Johansyah; Isti Siti Saleha Gandana (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2023)
In 2020, the unpredictable COVID-19 pandemic shook many parts of the world, including Indonesia. The pandemic affected almost all walks of life, and the education world was no exception. This study aims to unravel the students’ emotions about online learning during the pandemic through metaphors in the poems they wrote. This study draws on theories of metaphors, and the data were gained from poems written by five second-year students majoring in English Language and Literature Program. The metaphors analyzed in the poems revealed that students generally had negative emotions towards online learning, leading to feelings of frustration, despair and demotivation. A number of external and internal factors contributed to such feelings among students. This study calls for the need to listen to students’ voices in order to create mutual understanding between teachers and students and to create a more enjoyable learning atmosphere.